Pengembangan Media Domat untuk Meningkatkan Pemahaman Konsep Pecahan pada Siswa Kelas II Sekolah Dasar - Meriska, Delia (UNIB Press, 2025)
This study aims to develop Domat media products, describe the feasibility, and practicality of Domat media development to improve understanding of the concept of fractions. This study uses a research and development (R&D) type that adapts the ADDIE model, namely analysis, design, development, implementation, and evaluation. Data collection techniques used are interviews with teachers to find out the needs, and teacher responses. In addition, it also uses student questionnaires to determine student needs and responses to Domat media to improve understanding of the concept of fractions. The data obtained were analyzed using the Aiken’s V. This development research produces a product in the form of Domat media to improve understanding of the concept of fractions. The feasibility of the material, and the graphics were declared feasible, as well as the practicality of the teacher's response, and the student's response was stated to be very practical.